Contribution à l’étude de l’effet antimicrobien de l’extrait hydroéthanolique de Rosmarinus officinalis L. (Romarin) sur la qualité de la viande ovine de race Ouled Djellal au cours de la conservation au froid à 4°C. - ABDALLAH, Ahlem (My University, 2020)
The objective of this present study is to follow the antimicrobial effect of the hydro-ethanolic extract of Rosmarinus officinalis.L growing spontaneously in the region of Naama-Algeria (Djebl sidi Aissa) against some meat alteration microorganisms during storage at 4°C. The phenolic extraction compounds from rosemary were carried out by macerating 10 g of plant material from the plant in a hydro-ethanolic solution. The solvent of the filtrate collected was evaporated and the crude extract was finally diluted with distilled water to 0, 20, 40, 60, 80 and 100%. Each batch, composed of 3 pieces of meat, was stored in a polystyrene tray and treated with one to the previous concentrations of Rosemarinus extract and kept cold at 4 ° C for 9 days. The measurements and controls concerned the dosage of total polyphenols and flavonoids in the extract and plant material of rosemary, the enumeration of the main germs of contamination of meat (total aerobic mesophilic flora, thermotolerant coliforms, Staphylococcus aureus, Pseudomonas aeruginosa, psychrotrophic flora) and antimicrobial tests for the two germs (Staphylococcus aureus and Pseudomonas aeruginosa) responsible for food poisoning including: direct contact method, disc method, Minimum Inhibitory and Bactericidal Concentrations (MIC and CMB). The results underwent analysis of variance and comparison of means according to the Newman and Keuls test. The hydro-ethanolic extract of Rosmarinus officinalis L is rich in phenolic compounds 431.65 mgEAG / g DM and less rich in flavonoids 2.167 mgEQ / g DM. This rosemary extract exhibited an interesting antimicrobial activity particularly against Staphylococcus aureus and Pseudomonas aeruginosa involved in food poisoning of rotten meats. In addition, the level of contamination by germs (total aerobic mesophilic flora, thermotolerant coliforms, Staphylococcus aureus, Pseudomonas aeruginosa, psychrotrophic flora) of meat treated in particular at high concentrations of 80 and 100% of plant extract. Was found to be very low compared to the untreated control meat. Adding undiluted pure rosemary extract as a natural additive extended the shelf life of the meat up to day 9 at 4 ° C.
Keywords: Rosmarinus officinalis.L; sheep meat; preservation; extracts; hydro-ethanolic; antimicrobial